2017
DOI: 10.18632/oncotarget.21746
|View full text |Cite
|
Sign up to set email alerts
|

The association of plasma fibrinogen with clinicopathological features and prognosis in esophageal cancer patients

Abstract: BackgroundNumerous studies have shown that plasma fibrinogen was linked to esophageal cancer (EC) risk. However, the clinical significance of plasma fibrinogen in EC patients remain unclear and need to be further clarified.ResultsA total of 2865 patients with EC from 11 published studies were included in this meta-analysis. The prognostic and clinical relevance of plasma fibrinogen were evaluated in EC patients. Statistical significance of the pooled hazard ratio (HR) was found for overall survival (OS), disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Conversely, Li et al 12 revealed that Fib was not associated with the OS of ESCC. Recently, two meta-analyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 . However, the present study revealed that Fib was not associated with CSS or OS in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Li et al 12 revealed that Fib was not associated with the OS of ESCC. Recently, two meta-analyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 . However, the present study revealed that Fib was not associated with CSS or OS in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have reported that plasma Fib was related to cancer progression and prognosis in various cancers [7][8][9] , the role of plasma Fib in EC remains controversial [10][11][12] . Recently, two metaanalyses revealed that plasma Fib was a prognostic indicator in patients with EC 13,14 . As a nutritional factor, albumin (ALB) reflected the nutritional status in a variety of cancers, including patients with EC 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of meta-analysis had reported the prognostic role of elevated plasma fibrinogen in a variety of tumors, including, epithelial ovarian cancer 50 , Renal Cell Carcinoma 51 , esophageal cancer 52 . To the best of our knowledge, this meta-analysis was the first study to systematically assess the prognostic value of plasma fibrinogen in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Newcastle-Ottawa Scale (NOS) was used for quality assessment [15,16]. A study with NOS scores ≥6 was considered as "high-quality" [16,17].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%